Improved choleretic effect of Benachio-F®-based formula enriched with fennel extracts - Hye Jin Cho; Jun Su Im; Yong Sam Kwon; Kyung Soo Kang; Tae Min Kim (The Korean Society of Animal Reproduction and Biotechnology, 2022)
Functional dyspepsia (FD) is a gastrointestinal disorder with diverse symptoms but no structural or organic manifestations. Benachio-F® (herein named 'BF-1') is an over-the-counter liquid digestive formulated with multiple herbal extracts, which has been reported to improve symptoms of FD. A total two experiments were conducted. First, we examined whether BF-1 can modulate the progression of FD through two experimental rat models. A total of three doses (0.3x, 1x, 3x of the human equivalent dose) were used. In the gastric emptying model, both 1x (standard) or 3x (3-fold-concentrated) BF-1 enhanced gastric emptying was compared with that of vehicle-treated animals. In a feeding inhibition model induced by acute restraint stress, treatment with 1x or 3x BF-1 led to a similar degree of restoration in food intake that was comparable to that of acotiamide-treated animals. Among the constituents of BF, fennel is known for its choleretic effect. Thus, we next investigated whether a novel BF-based formula (named 'BF-2') that contains an increased amount of fennel extract (3.5-fold over BF-1), has greater potency in increasing bile flow. BF-2 showed a superior choleretic effect compared to BF-1. Furthermore, the postprandial concentration of serum secretin was higher in animals pretreated with BF-2 than in those pretreated with BF-1, suggesting that the increased choleretic effect of BF-2 is related to secretin production. Our results demonstrate that BF-1 can modulate the pathophysiological mechanisms of FD by exerting prokinetic and stress-relieving effects, and that BF-2 has a better choleretic effect than BF-1.